2020
DOI: 10.1002/bsl.2490
|View full text |Cite
|
Sign up to set email alerts
|

Understanding expert testimony on child sexual abuse denial after New Jersey v. J.L.G.: Ground truth, disclosure suspicion bias, and disclosure substantiation bias

Abstract: The New Jersey Supreme Court held in New Jersey v. J.L.G. (2018) that experts can no longer explain to juries why sexually abused children might deny abuse. The court was influenced by expert testimony that "methodologically superior" studies find lower rates of denial. Examining the studies in detail, we argue that the expert testimony was flawed due to three problems with using child disclosure studies to estimate the likelihood that abused children are reluctant to disclose abuse: the ground truth problem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
(121 reference statements)
0
14
0
Order By: Relevance
“…Victims of (child) sexual abuse might deny their traumatic experiences. While there is currently a discussion surrounding the prevalence of false denials in child sexual abuse investigations (London et al., 2020; Lyon et al., 2020), there is agreement that children often delay disclosure, and might initially deny that any abuse took place before coming forward (Eisen et al., 2021; London et al., 2020). When they eventually talk about the abuse, these victim's memory statements serve as important pieces of evidence in court and can influence decisions surrounding culpability (Romeo et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Victims of (child) sexual abuse might deny their traumatic experiences. While there is currently a discussion surrounding the prevalence of false denials in child sexual abuse investigations (London et al., 2020; Lyon et al., 2020), there is agreement that children often delay disclosure, and might initially deny that any abuse took place before coming forward (Eisen et al., 2021; London et al., 2020). When they eventually talk about the abuse, these victim's memory statements serve as important pieces of evidence in court and can influence decisions surrounding culpability (Romeo et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also possible that false denials are more prevalent than previously given credit for. That is, London et al (2008) showed that in child sexual abuse cases, victims rarely deny the event when they contact the authorities suggesting that false denials are not that commonly used (but see also Lyon et al, 2020). However, our results point towards the idea that in everyday life people lie one or multiple times a day, and often tend to use false denials as their deceptive strategy as opposed to fabrication or feign amnesia.…”
Section: Discussionmentioning
confidence: 56%
“…Children largely answer Yes-No questions “yes” or “no” without elaboration and rarely answer “I do not know” or seek clarification (Stolzenberg & Lyon, 2014). In the investigation of sexual abuse, a failure to disclose touching has different practical implications than an overt denial, because researchers generally agree that children delay disclosing sexual abuse, but there is disagreement over the likelihood that children deny sexual abuse when directly questioned (London et al, 2020; Lyon et al, 2020).…”
Section: Developing Definitions Of Touchmentioning
confidence: 99%